ANALISIS PENGARUH INFLASI DAN SUKU BUNGA INDONESIA (SBI RATE) TERHADAP HARGA SAHAM PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B11110095, Meisyana (Jurnal Manajemen Update, 2014)
Capital markets have an important role for the economy of a country because capital markets work in two ways: first as a means for companies to obtain funds from investors (investors). Second, capital markets became a means for people to invest in financial instruments such as stocks, bonds, mutual funds, and others. Many types of securities (securities) are sold in the market, one of them is stock. So this study focuses on the analysis of Inflation And Interest Rate Effects of Indonesia (SBI rate) Share Price On The Banking Sector Listed in Indonesia Stock Exchange. The problem in this study are Is the level of Indonesian inflation and interest rates affect stock prices in the banking sector in Indonesia Stock Exchange. The technique uses random sampling with a sample of 10 companies from 36 companies sub-sector banks listed on the Indonesia Stock Exchange during the period 2008 to 2012, collecting data using secondary data published by the Indonesia Stock Exchange via the Internet. As for the use of analysis techniques ststistik test using SPSS. The results of this study concluded that the variable is inflation and interest rates simultaneously (simultaneous) effect on stock prices. Key words :Â  inflation, interest rates and stock prices.